Association between Diabetes and Tooth Loss in Dental Patients- A Case-control Study (Journal of Dentistry and Allied Science, 2025)
Background and objectives: The prevalence of diabetes is increasing day by day. People with diabetes are at greater risk for oral health problems. Destructive features of periodontal disease are more common in diabetics. Tooth loss is a result of periodontal disease. This study aimed to determine the association between diabetes and tooth loss in dental patients. Materials and methods: A matched case-control study was conducted where dental patients with tooth loss were the cases, and those with no tooth loss were in the control group. A total of 144 samples, 48 samples for the case group and 96 samples for the control group were selected by consecutive sampling technique. After completing informed consent, data were collected in two different phases. Data were collected by face-to-face interview method using a semi-structured questionnaire. After data collection, data were analyzed using Statistical Package for Social Studies (SPSS) version 22. Result: The mean±Sd of age for the dental patients with tooth loss group it was 54.42±10.952 and for the dental patients without tooth loss, it was 50.06±8.228. 54% (26) for the case and 53% (51) for the control were male and females were 46% (22) and 47% (45) respectively in the case and control groups. Dental patients aged 45 to 56 years old had a higher prevalence of diabetes. 66.7% of dental patients with tooth loss were diabetic, and 36.5% of dental patients without tooth loss were diabetic. 50% of diabetes patients with tooth loss had diabetes for 5 years. In this study, we found that there was a significant association between tooth loss and the presence and duration of diabetes and the odds ratio (95% CI) was 3.486 (1.680-7.233). Conclusion: With the limitation of the study, it can be concluded that diabetes may be a risk factor for tooth loss. Duration diabetes can increase the risk of tooth loss.Journal of Dentistry and Allied Science, Vol. 7 No 2: 26-32